EKOTEOLOGI DI PESANTREN: INTEGRASI SPIRITUALITAS DAN INOVASI EKOBRIK DI DARUL ULUM JOMBANG - Rosyidah, Yulia Nur; Rosidah, Feryani Umi (Universitas Islam Negeri Sunan Ampel, 2025)
This study explores plastic waste management through the use of ecobricks at Darul Ulum Islamic Boarding School, Jombang, from the perspective of environmental theology. The research highlights the lack of studies on the integration of spiritual values and sustainability practices in Islamic boarding school environments. A qualitative approach was employed using observation, interviews, and documentation techniques. The analysis is grounded in Sayyed Hossein Nasr’s theory of ecotheology, which views nature as a manifestation of the Divine, rather than a mere object of exploitation. The findings reveal that the ecobrick program is carried out participatively by students through systematic stages: collecting, cleaning, cutting, compressing plastic into bottles, and constructing functional items. As a result, plastic waste is transformed into usable products such as tables, chairs, and decorations. Beyond its ecological impact, the program also strengthens character education and spiritual awareness of the environment.